ضوابط التعامل المنهجي مع المخطئين دراسة قرآنية Rules for systematic dealing with wrongdoers, a Qur’anic study - Elatrash, Radwan Jamal Yousef; Farooq Omar, Ahmed (Halabja University, 2020)
This research is focusing on the Quranic rules and regulations in dealing with human error, whether it is an individual or collective error. The human is a weak creature, shortcomings are in his nature, composed of feelings that are difficult to control, and thus, this deficiency and these feelings implicate him in mistakes and excesses toward others. And because of lacking skills of dealing with errors and resolving them; greatly maximized small errors, and minimizing big errors. Since the types of wrongdoers are not alike, some of them make mistakes knowingly and insistently, and some of them make mistakes about negligence and negligence,, so this paper tries to take a closer look at what is written in the book of our Lord Almighty verses on this subject, to guide us to the parameters of the correct approach in dealing with the wrongdoers. The research will depend on the inductive and analytical approach. It is expected that the research will lead to extracting systematic rules from the spirit of the verses for dealing with the wrongdoers